Site index for Cedrela odorata L. in coffee agroforestry systems in Pérez Zeledón, Costa Rica - Carvajal-Arroyo, David (2022)
The study objective was to determine the site quality for Cedrela odorata L. in coffee Agroforestry Systems, using anamorphic site index curves based on a simple regression model. The foregoing, because the productive capacity of a site is one of the determining factors for the yield and timber production of any forest species. The study was carried out in Pérez Zeledón, Costa Rica on coffee farms with C. odorata trees between 1 and 20 years old. 140 plots of 1 000 m2 and a total of 2 155 individuals were sampled, of which 391 were selected as dominant trees. From this sample, six dominant height prediction models were developed as a function of age and the respective site index curves were generated. The best model was Hdom = exp (1.15993 + 0.778002 * ln (Age)) whose determination coefficient was 0.87, this model was selected as the guide curve. They were cross-validated to the total volume per hectare to determine the best curves set.  The best set of curves was the common slope, and five classes of IS were obtained (15, 17, 19, 21, and 23 m), at a base age of 10 years. At 20 years, the sites with the lowest productivity project a dominant height of 25.7 m, while those with the highest yield project up to 39.4 m